(untitled) (Itinera, 2014)
This article is an historical analysis of Saint Paul´s letters as Kantian source, not only in the context of the Kantian philosophy of religion but also and especially of his practical philosophy overall. In order to clarify the context of this analysis, this contribution is split into two parts. The first part cares to analyze the value of Saint Paul within the historical background of Kant, highlighting why it is reasonable to assume an influence of Saint Paul in the second Critique. The second part, therefore, engages a direct confrontation with the Critique of practical reason, using the learnings provided by the first section. The final aim of this work is to discuss the possibility of welcoming a new portrait of Kant with strong biblical traits is some key moments of his practical philosophy.